Anomalous Origin of the Left Coronary Artery From the Pulmonary Artery: An Uncommon Coronary Anomaly With Serious Implications in Adulthood. (January 2017) - Gangadharan, Venkat; Sivagnanam, Kamesh; Murtaza, Ghulam; Ponders, Michael; Teixeira, Otto; Paul, Timir
A 36-year-old woman was seen with complaints of exertional chest pain and shortness of breath. Her medical history included atrial fibrillation and diabetes. Physical examination was unremarkable except for an irregular cardiac rhythm. Myocardial perfusion imaging revealed the presence of a large area of infarction involving the entire anterior and apical walls and part of the anteroseptal wall with minimal periinfarct ischemia. Computed tomography coronary angiogram revealed an anomalous left main coronary artery arising from the main pulmonary artery. Right and left heart catheterizations demonstrated moderate pulmonary hypertension with a slight step-up in oxygen saturation between the right ventricle and main pulmonary artery. Coronary angiography showed a large tortuous right coronary artery with collaterals to the left anterior descending artery that drained into the main pulmonary artery. She was referred for surgery. This case demonstrates a rare coronary artery anomaly in an adult where survival is dependent on collateral circulation.